Correlation of protein content and other nutritions in human diet - Yermishev, O. V.; Rudkevych, A. K.; Luka, O. S. (Journal of Education, Health and Sport, 2020)
To identify correlations between protein content and other components of the diet we evaluated the actual diet using method of analyzing frequency of food consumption (for two months) of 68 persons of different ages and genders. The results of our studies revealed the ratio of protein and energy in the actual diets of the surveyed respondents which was a fairly stable value ranging from 3.03 ± 0.07 g/kcal in respondents aged 46 to 65 years to 3.75 ± 0.09 g/kcal in the group surveyed individuals aged 11 to 14 years. Due to the fact that in the age group of 15 to 23 years 48 % of the respondents were found to be deficient in protein and energy below the approved standards, further correlation analysis of the content of protein and other nutrients in the diet was performed in this group. The respondents of this group were divided into 6 experimental groups according to the content of protein and energy in the diet. Our studies revealed strong positive correlations between protein and energy content and protein and fats content in the diet with average correlation coefficients of 0.66 and 0.46, respectively, and a low correlation between protein and carbohydrates content, the correlation coefficient was 0.16. Analysis of the structure of the actual diet revealed strong positive correlations of protein with B6 and B12 vitamins of the diet and lack of correlation with vitamins A and C in all the experimental groups. When analyzing correlations between content of protein and mineral elements of the diet we revealed strong positive correlations with an average correlation coefficient of 0.65 between protein and phosphorus and 0.36 between protein and sodium (0.36) as well as weak correlations with potassium, calcium and magnesium with correlation coefficients of 0.3, 0.25, and 0.22, respectively.